A novel defect detection method for software requirements inspections - Bilal Alqudah; Laiali Almazaydeh; Reyad Alsalameen (Institute of Advanced Engineering and Science, 2023)
The requirements form the basis for all software products. Apparently, the requirements are imprecisely stated when scattered between development teams. Therefore, software applications released with some bugs, missing functionalities, or loosely implemented requirements. In literature, a limited number of related works have been developed as a tool for software requirements inspections. This paper presents a methodology to verify that the system design fulfilled all functional requirements. The proposed approach contains three phases: requirements collection, facts collection, and matching algorithm. The feedback results provided enable analysist and developer to make a decision about the initial application release while taking on consideration missing requirements or over-designed requirements.